[LB.03.05] NEGATIVE CORRELATION OF RHO-MIR-15-5P AND MAP3K IN HYPERTENSIVE RAT MODELS. (September 2017) - Tekin, G.; Gul, A.; Karakurt, S.
Abstract : Objective: Hypertension characterized by elevated systemic blood pressure is an undisputable risk factor for heart failure and renal disruption. In vitro and in vivo studies established that alterations in microRNAs (miRNAs) levels are decisive for gene expression in various pathological conditions including cardiovascular diseases as well as renal disruption. In our study, we aimed to investigate the interaction of miRNAs and expression of MAPK3 / ERK (mitogenic activated protein kinase 3) which is one of the crucial members of the aldosterone metabolism signaling pathway in the pathogenesis of hypertension. Design and method: During the in vivo studies, hypertension animal model was constructed by using Wistar albino rats (150 g) via subcutaneous injection of 0.75 μM/kg/day of aldosterone while a physiological saline solution was injected to the control group. Measurements of systolic blood pressure were performed by Tail-cuff method during 3 weeks. The aldosterone levels of rat blood samples were measured by ELISA. RNA integrity and concentration were measured by using Agilent RNA 6000 Nano kit and the samples which have RIN value more than 7 were used miRNA array and microarray studies. Validation of expression was performed with qR-PCR. In order to detect protein expression of MAPK3, western blot analyses were performed. Results: The mRNA expression of the membrane protein MAP3K highly increased in both the kidney (1.7-fold; (p < 0.001)) and heart (2.7-fold; (p < 0.0001)) of rats with hypertensive. The rno-miR-15a-5p expression was down-regulating by 75% (p < 0.0001) in both tissues. Conclusions: Importantly, rno-miR-15a-5p was initially identified as a negative regulator of aldosterone metabolism. Interpretation of the data and further extensive insights into the targeting of miRNAs, particularly rno-miR-15a-5p, in hypertension can be found is linked causally to the repression of the MAPK3 through the upregulating of rno-miR-15a-5p in hypertension. Taken together, these data suggest that rno-miR-15a-5p is involved in aldosterone-induced hypertension, providing a new perspective in hypertensive disease mechanisms.